(untitled) (Journal of the College of Basic Education, 2022)
To know the English Language ,one must know the grammer of it . There are many ways of thinking about grammer .Many senses in which the term is used .One Way is that grammer is something that produces thae sentences of a Language .Then we may ask what we mean by something .An English grammer would be a set of rules for making English sentences, thus something might mean the rules or we can have another meaning for something , we can simply mean a speaker of English Aitchison (1999:181) quotes Roger’s Bacon view about the importance of grammer far as the essential properties of grammer are concerned .Nunan (1999:96) affirms that for most people who speak a language ,the essence of that language lies in grammer.The object of grammer is to teach people to express their thoughts correctly, either in speech or writing .